Uji Sitotoksisitas Seng Oksida Ekstrak Allium Sativum Linn. terhadap Sel Fibroblas Gingiva Manusia - Nisrina Qurrota Aini; Titien Hary Agustantina; Devi Rianti (Jurnal Material Kedokteran Gigi, 2019)
The use of zinc oxide eugenol in open pulps is controversial because of the cytotoxic effects of eugenol. Previous research has proven that zinc oxide Allium sativum Linn. extract can be an alternative for pulp capping material because it has antibacterial effect. The materials that applied to the oral cavity must be non-cytotoxic and biocompatible, therefore cytotoxicity testing is required of zinc oxide Allium sativum Linn. extract on human gingival fibroblast cell. To determine the cytotoxicity of zinc oxide Allium sativum Linn. extract on human gingival fibroblast cell. Cytotoxicity test of a mixture of zinc oxide with Allium sativum Linn. extract using ratio 1:1 (group A) and 2:1 (group B), zinc oxide eugenol 1:2 (control group C). Each material is exposed to the human gingival fibroblast cells. The cytotoxicity test was tested using an MTT essay test. The density of optic formazan indicated the number of living cell. Cytotoxicity parameters using IC50. Data were analyzed using one-way Anova test and Tukey HSD test. The number of living cells in group A= 40,400 %, group B= 50,613 % and group C= 51,247 %. There was no significant difference between zinc oxide Allium sativum Linn at a ratio of 2:1 (group B) with zinc oxide eugenol 2:1 (group C). Zinc oxide Allium sativum Linn. extract with a ratio 2:1 were not cytotoxic toward human gingival fibroblast cell.